PENGARUH LAYANAN BIMBINGAN INFORMASI TERHADAP PENURUNAN KEBIASAAN BERMAIN GAME - Kurnia Ade Utama, Muhammad Bogy; Kusumaningtyas, Lydia Ersta (UNIVERSITAS SLAMET RIYADI, 2017)
ABSTRACTThe aim of this researcher is to find out whether there is an influence of information guidance services on the decline in game playing habits in class X students at SMA N 6 Surakarta 2017/2018 Academic Year. The population in this study were all students of class X in SMA N 6 Surakarta in the Academic Year 2017/2018, amounting to 361 students. while the sample used was 33 students, the data collection technique used a questionnaire to decrease the habit of playing games in class X students at SMA N 6 Surakarta to students through two stages, namely before and after being given information guidance then to analyze the data using the t-test formula. Based on the results of data analysis about the effect of information guidance services on decreasing game playing habits in class X students at SMA N 6 Surakarta in the Academic Year of 2017/2018, it was obtained that the t value was = 7.224, then consulted with t table with db = (N-1) = (33-1) = 32 in the significance level of 5% and 1%. So it can be concluded that t count is greater than t table or 2.037 <7.224> 2.738. Thus the hypothesis that reads